Fabrication and evaluation of carbocisteine-loaded solid lipid nanoparticles to treat pulmonary infections - Rane, Bhushan R.; Jain, Ashish S.; Mane, Nikita P.; Patil, Vaibhav; Patil, Mukesh S.; Bavaskar, Kedar R. (Creative Pharma Assent, 2024)
Background: Solid lipids Nanoparticles (SLN) comprise physiological and biocompatible lipids. SLN is an alternative carrier system to polymeric nanoparticles or liposomes. It has been claimed that SLN offers combined advantages and avoids the disadvantages of other colloidal carrier systems. Aim: The research aims to fabricate and evaluate the carbocisteine solid lipid nanoparticles loaded in situ gel. Methodology: SLN was prepared by using glycerol monostearate as a solid lipid and by high-pressure homogenization (Panda plus 2000) method using poloxamer 188 as a stabilizer to improve its bioavailability and reduce particle size. The quality-by-design concept was used to develop the SLN by optimizing process variables. Result and discussion: The drug and excipient compatibility study was checked using FTIR, and no interaction between both was found. Optimized SLN of carbocisteine were evaluated for zeta potential, particle size, and % drug release, found results as -19.67 mv, 50 to 200 nm, and up to 70.84%, respectively. Optimized gel batches were also evaluated for the stability study. Conclusion: All the batches were evaluated for various parameters. The F6 batch was optimized based on particle size, stability, Zeta potential, and release pattern. SLN could provide a better advantage of good penetration and targeting to treat pulmonary disease.